Efficacy and safety of the therapeutic cancer vaccine tecemotide (L-BLP25) in early breast cancer: Results from a prospective, randomised, neoadjuvant phase II study (ABCSG 34). (June 2020) - Singer, Christian F.; Pfeiler, Georg; Hubalek, Michael; Bartsch, Rupert; Stöger, Herbert; Pichler, Angelika; Petru, Edgar; Bjelic-Radisic, Vesna; Greil, Richard; Rudas, Margaretha; Maria Tea, Muy-Kheng; Wette, Viktor; et al.
Abstract: Background: Immune-based strategies represent a promising approach in breast cancer (BC) treatment. The glycoprotein mucin-1 (MUC-1) is overexpressed in more than 90% of BC patients, and is targeted by the cancer vaccine tecemotide. We have investigated the efficacy and safety of tecemotide when added to neoadjuvant standard-of-care (SoC) treatment in early BC patients. Patients and methods: A total of 400 patients with HER2-early BC were recruited into this prospective, multicentre, randomised 2-arm academic phase II trial. Patients received preoperative SoC treatment (chemotherapy or endocrine therapy) with or without tecemotide. Postmenopausal women with oestrogen receptor (ER)+++, or ER++ and Ki67 < 14%, and G1, 2 tumours ('luminal A' tumours) received 6 months of letrozole. Postmenopausal patients with triple-negative, ER−/+/++ and Ki67 ≥ 14%, and with G3 tumours, as well as premenopausal patients, received four cycles of epirubicin/cyclophosphamide plus four cycles of docetaxel. Primary end-point was residual cancer burden (RCB; 0/I versus II/III) at surgery. Secondary end-points included pathological complete response (pCR), safety, and quality of life. Findings: We observed no significant difference in RCB 0/I rates between patients with (36.4%) and without (31.9%) tecemotide in the overall study population ( p  = 0.40) nor in endocrine and chemotherapy-treated subgroups (25.0% versus 13.3%, p  = 0.17; 39.6% versus 37.8%, p  = 0.75, respectively). The addition of tecemotide did not affect overall pCR rates (22.5% versus 17.4%, p  = 0.23), MUC-1 expression, or tumour-infiltrating lymphocytes content. Tecemotide did not increase toxicity when compared to SoC therapy alone. Interpretation: Neoadjuvant tecemotide is safe, but does not improve RCB or pCR rates in patients receiving standard neoadjuvant therapy. Highlights: Largest vaccine trial in preoperative treatment of early breast cancer. MUC-1–based tecemotide vaccine is safe but did not show an improved treatment effect when added to preoperative SoC. Endocrine therapy increases and chemotherapy decreases intratumoural TILs, whereas tecemotide has no effect on TILs.